SWOT Analysis of Padang City MSMEs in the Pandemic Era Covid-19 - Irda Irda; Reni Yuliviona; Elfitra Azliyanti; Dahliana Kamener (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze a competitive strategy for small and medium business actors in the city of Padang during the Covid-19 pandemic. The observation process was carried out on small and medium enterprises spread across eleven sub-districts in the town of Padang. Respondents in this study were small and medium enterprises in Padang with a total sample of 131 with a sampling technique using the quota sampling method. The analysis technique used is IFA, EFA, SWOT, and QSPM analysis. Based on the study results, it can be concluded that the first quadrant looks to be prioritized and used as a strategy (SO). Strategy (ST) improves product quality to anticipate competitors from within the province and other regions. Strategy (WO) is implemented by encouraging business stability. Strategy (WT) in participating in banking programs to increase creative business.